2005
DOI: 10.1002/jsfa.2359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of CO2 on the antioxidant content and the polyphenol oxidase activity of ‘Rocha’ pears during cold storage

Abstract: Pears (Pyrus communis L. cv. 'Rocha') were exposed to air or controlled atmosphere (CA) containing various concentrations of CO 2 : 0, 0.5 and 5 kPa, all with 2 kPa O 2 . After 4 months of storage at 2 • C, the fruits were transferred to air at room temperature, and assessed in terms of soluble solids, titratable acidity, pH, incidence of brown heart and flesh browning, phenolic content, vitamin C content and polyphenol oxidase activity. By 4 months of storage, soluble solids and pH increased, and acidity decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The experimental results indicated that GSH could be playing an important role in acquisition of chilling tolerance in Japanese plums leading to lower CI incidence and severity. This role could be quite similar to the one ascribed to AsA in pears (Veltman et al ., ; Larrigaudiére et al ., ; Galvis–Sánchez et al ., ). More research is required to elucidate the role of GSH in the development of various physiological disorders in fruits.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The experimental results indicated that GSH could be playing an important role in acquisition of chilling tolerance in Japanese plums leading to lower CI incidence and severity. This role could be quite similar to the one ascribed to AsA in pears (Veltman et al ., ; Larrigaudiére et al ., ; Galvis–Sánchez et al ., ). More research is required to elucidate the role of GSH in the development of various physiological disorders in fruits.…”
Section: Resultsmentioning
confidence: 97%
“…DHA concentrations increased significantly during ripening period after both storage intervals which is in agreement with Galvis–Sánchez et al . () who reported a similar increase in DHA during shelf life of ‘Rocha’ pears following 4 months of CA storage. The activities of enzymes involved in oxidation and recovery of AsA were determined to explain the dynamics of oxidised and reduced forms of AsA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Browning disorder of pears is affected by both preharvest factors (such as picking date, maturity, fruit size and kind of fruit-bags) and postharvest factors (such as the duration of cooling period, the storage temperature and the CO 2 and O 2 concentrations; Lammertyn et al, 2000; Guan et al, 2005, 2008; Galvis-Sánchez et al, 2006; Wang and Wang, 2011). For example, pears with higher content of chlorogenic acid, a dominant phenolic acid in ‘Huangguan’ pears, are prone to browning (Franck et al, 2007; Kou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the occurrence of surface browning in ‘Huangguan’ pear was also reported to be related to the Ca 2+ deficiency and the cellular Ca 2+ distribution in skin tissues (Dong et al, 2015). In addition, heart browning and flesh browning of ‘Rocha’ pears are increased by the combination of 2 kPa O 2 + 5 kPa CO 2 (Galvis-Sánchez et al, 2006). …”
Section: Introductionmentioning
confidence: 99%